2000
DOI: 10.1007/s002130000508
|View full text |Cite
|
Sign up to set email alerts
|

Appetitive effects of drug cues modelled by pictures of the intake ritual: generality of cue-modulated startle examined with inpatient alcoholics

Abstract: New techniques of measuring drug cue motivation indicate that drug cues may have incentive properties in individuals in treatment for alcoholism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
47
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 20 publications
10
47
0
1
Order By: Relevance
“…This is in line with incentive theories of addiction proposing that drug associated cues are processed as appetitive or motivational incentives (Robinson and Berridge, 2000;Stewart, 1983;Wise, 1988). Incentive theories of drug addiction have been confirmed for other drugs, e.g., nicotine (Dempsey et al, 2007;Geier et al, 2000;Rehme et al, 2009) and alcohol (Grüsser et al, 2002;Heinz et al, 2003;Mucha et al, 2000), but results for heroin cues were undetermined so far. Walter et al (2011) did not find a difference in startle response between neutral and drug-related stimuli, but opposed to our study, they used less specific and standardized drug pictures.…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…This is in line with incentive theories of addiction proposing that drug associated cues are processed as appetitive or motivational incentives (Robinson and Berridge, 2000;Stewart, 1983;Wise, 1988). Incentive theories of drug addiction have been confirmed for other drugs, e.g., nicotine (Dempsey et al, 2007;Geier et al, 2000;Rehme et al, 2009) and alcohol (Grüsser et al, 2002;Heinz et al, 2003;Mucha et al, 2000), but results for heroin cues were undetermined so far. Walter et al (2011) did not find a difference in startle response between neutral and drug-related stimuli, but opposed to our study, they used less specific and standardized drug pictures.…”
Section: Discussionsupporting
confidence: 84%
“…The affectmodulated startle methodology has been repeatedly used in drug research by including photographs of drug paraphernalia or drug intake rituals and measuring the suppression of the startle response by drug-related scenes relative to neutral scenes (referred to as cue-related startle suppression, CSS). In general, these studies confirmed incentive theories because they consistently reported CSS in addicted users of alcohol or nicotine while viewing drug-related cues (Cinciripini et al, 2006;Dempsey et al, 2007;Geier et al, 2000;Mucha et al, 2000).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Examples of responses that can occur before craving is reported include neurophysiological arousal to alcohol cue exposure. In a recent study abstinent alcoholics, who reported little subjective response to alcohol-related cues, had a strong inhibition of startle responses, which reflect relatively automatic rather than cognitive processes (Mucha et al, 2000). This type of automatic response below conscious awareness might reflect an important drive for using cocaine and be detected using functional brain imaging with BOLD-MRI during the initial 30 s of exposure to videotape cocaine cues.…”
Section: Introductionmentioning
confidence: 92%
“…We have found early behavioral differences when positive and negative faces were viewed as well (Eisenbarth and Alpers, in press; Eisenbarth, Gerdes, and Alpers, in press). However, it should not be overlooked that there are exceptions from the rule that high arousal is needed for startle attenuation (drugrelated cues with low arousal: Geier et al, 2000;Mucha et al, 2000).…”
Section: Arousal Differences Between Scenes and Facesmentioning
confidence: 99%